The Khlysts in Kharkiv Province in the 19th century: The Problem of Exposing and Combating the Spread of Sects from the State and the Official Church (on the settlement Popivka of Starobil’sk County example) - Арзуманова, Тетяна (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2016)
The article deals with the problem of exposure and investigation of secret religious persuasions in Kharkiv province in the 19th century (on the Khlysts sect example). The author draws the conclusion about the complexity of this process due to the closedness and seclusion of the sect members, their exclusion from public life, the lack of cohesion among the representatives of the secular and spiritual authorities in the investigation of such cases. Difficulties in identifying the religious sects led to the failure to identify the true guilt of the suspected and the relevant punishment, the dissemination of offensive rumors and gossip about the suspects.